Peta Usaha Kecil Menengah (UKM) Jalan Syahdan sebuah Hasil Penelitian Proyek Workshop Do Good Indonesia - Wulandari, Sari (Bina Nusantara University, 2011)
Syahdan Small Medium Enterprises (SME) map around the campus BINUS Syahdan Syahdan precisely along the streets and alleys that connect with it, ranging from Seven-Eleven to Circle K, which has become the backbone of student activities on campus so as to facilitate students in accessing the small business as well as media liaison for SMEs to communicate with the target market. The research was conducted referring to the science of Visual Communication Design Discipline. The purpose and benefits of this research is to use scientific and practical the SME Map of Jalan Syahdan and research results in the form of advice which are based on Cognitive Principle for ID member, Communication Principles for ID member, which is based on ease of implementation, the function of information for ID, which will tell us the effectiveness of media communications, and aesthetics. It is expected that the information in it will be delivered properly, can bring out the character right BINUS University and establish a positive image in the mind of the reader. In the results of this study will be presented the data and advice needed as a reference by them who will develop the SME Map of Jalan Syahdan.